Overnight interbank markets and the determination of the interbank rate: a selective survey - Green, Christopher J.; Bai, Ye; Murinde, Victor; Ngoka, Kethi; Maana, Isaya; Tiriongo, Samuel (Elsevier, 2016)
Overnight interbank markets provide critical facilities for the banking system to manage, pool and redistribute its cash reserves. We provide a selective survey of the literature on overnight interbank markets. We outline the typical structure of overnight markets, including the networking relationships involved, as an indispensable prerequisite for a clear understanding of the workings of these markets. We review the theoretical and empirical studies on the determination of the overnight rate, and in that context discuss the implications of the 2007–08 financial crisis. We summarise key issues for further research.